Formal act of defection from the catholic church: Canons 751; 1364 (Roman Replies and CLSA Advisory Opinions 2008, 2008)
"The following letter clarifies some aspects of an earlier circular letter by the President of the Pontifical Council for Legislative texts concerning the requisites for the formal act of defection that releases a baptized Catholic from the impediment of disparity of cult, the prohibition of mixed marriage, and the obligation of canonical form for the validity of a marriage. John Huels noted in April 2008 in a list-serv discussion: "The 13 March 2006 circular letter of the Pontifical Council for Legislative Texts made it clear that a formal act of defection had to be received by a competent Catholic ecclesiastical authority. The act of reception by the Catholic authority is a constitutive element of the formal act of defection. It applies retroactively, affecting marriages since the 1983 Code entered into force." The following reply offers a clarification of the requisites."